Pelatihan Pembuatan Soal Matematika Berbasis CTL dan Penggunaan Aplikasi Pembelajaran Online di SMA Adabiah Padang - Hafizah Delyana; Ainil Mardiyah; Ali Asmar (LPPM Universitas Bumigora, 2022)
Mathematics is one of the subjects that students find difficult, especially for the mastery of realistic questions or in the form of story problems. These questions are included in CTL-based or contextual questions. Contextual problem is a question that links the material with real-world situations and encourages students to make connections between the material they teach and its application in their daily lives. Mathematics teacher at SMA Adabiah has difficulty designing CTL-based math problems. In addition, during this pandemic, teachers had difficulty giving questions online because face-to-face was not possible. For this reason, teachers are required to have creativity so that learning can be understood by students. Mathematics teachers are given training that supports this. The training that will be provided is in the form of making questions using an online learning application. Teachers who take part in the training are expected to be able to motivate and evaluate students' ability to work on contextual questions even though they are carried out online.